Inovasi Pendidikan Melalui Pendekatan Sistem di MTS Parmiyatu Wassa’adah - M, Maulidayani; Fitri, Adelia; Ardiansah, Mulia; Azzahrah, Nindya; Harahap, Yusuf Ali Ahmad (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research is about "Educational Innovation Through a Systems Approach at MTS Parmiyatu Wassa'adah". This research method is descriptive qualitative research. This research is located at MTS Parmiyatu Wassa'adah. The subject of this research is the School Principal. The research used is observation, interviews and documentation. Educational innovation through a systems approach has become the main focus in educational transformation in schools. This approach aims to integrate various educational components, including curriculum, technology, school management, stakeholders, and learning processes, into a coherent and effective system. This innovation not only creates a more dynamic and inclusive learning environment, but also enables improved student learning outcomes.